The Impact of Soft Leadership Skills on Organizational Longevity: An Analytical Research at the Ministry of Higher Education and Scientific Research - Helal , Samar; Saeed , Hadeel (Journal of Economics and Administrative Sciences, 2025)
The research studies the effect of soft leadership skills on organizational longevity within the Ministry of Higher Education and Scientific Research. The study seeks to diagnose the effectiveness that leadership competency may have in communication, initiatory capability, training, and team building for the sustenance of institutional performance and adaptability. Using a descriptive-analytical approach, data were collected using a structured questionnaire from 120 administrative leaders. The questionnaire was adapted from validated scales, while the analysis was conducted through SPSS and AMOS software. There was a statistically significant positive association with some of the soft skills of leadership towards organizational longevity, with communication, training, and team-building skills considered to exert the maximum influence. The results also revealed that the study model accounted for 74% of the variance in organizational longevity, clearly indicating the strategic importance of non-technical leadership traits in building resilience, innovativeness, and long-term success of an institution. These findings imply that the development of soft leadership skills should hence be embedded in leadership development and organizational strategy. This research contributes to the continuing discourse on public-sector leadership and provides useful recommendations to promote institutional sustainability in higher education systems. Focusing on soft leadership as a process of transformation, this study tries to inform policy and practice in managing higher education.